2011
DOI: 10.1093/nar/gkr532
|View full text |Cite
|
Sign up to set email alerts
|

Specific sequence determinants of miR-15/107 microRNA gene group targets

Abstract: MicroRNAs (miRNAs) target mRNAs in human cells via complex mechanisms that are still incompletely understood. Using anti-Argonaute (anti-AGO) antibody co-immunoprecipitation, followed by microarray analyses and downstream bioinformatics, ‘RIP-Chip’ experiments enable direct analyses of miRNA targets. RIP-Chip studies (and parallel assessments of total input mRNA) were performed in cultured H4 cells after transfection with miRNAs corresponding to the miR-15/107 gene group (miR-103, miR-107, miR-16 and miR-195),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…These targets include loci in the protein-coding region of mRNAs (8)(9)(10)(11)(12)(13), 5′ UTRs (14), intronic and intergenic transcripts (15,16), and other non-protein-coding RNAs (ncRNAs) (17,18), as well as embedded B retroelements (13,19), pseudogenes (20), short interspersed elements (SINEs) (21), and circular RNAs (22,23). As technological and research advances reveal a larger and more diverse spectrum of miRNA targets, the related question of how many miRNAs are encoded by an organism's genome becomes one of renewed importance.…”
Section: Significancementioning
confidence: 99%
“…These targets include loci in the protein-coding region of mRNAs (8)(9)(10)(11)(12)(13), 5′ UTRs (14), intronic and intergenic transcripts (15,16), and other non-protein-coding RNAs (ncRNAs) (17,18), as well as embedded B retroelements (13,19), pseudogenes (20), short interspersed elements (SINEs) (21), and circular RNAs (22,23). As technological and research advances reveal a larger and more diverse spectrum of miRNA targets, the related question of how many miRNAs are encoded by an organism's genome becomes one of renewed importance.…”
Section: Significancementioning
confidence: 99%
“…“RIP-ChIP” (AGO protein immunoprecipitation, which pulls down miRNAs and mRNA targets, followed by high density microarray) revealed that members of the miR-103/107 family preferentially bind their target CDS [19]. Individual miRNAs also recognize CDS targets.…”
Section: Mirna Biogenesis and Regulationmentioning
confidence: 99%
“…Until recently, active animal miRNA recognition sites were thought to be present solely within the 3’ UTR of an mRNA. However, recent evidence has suggested that sites also exist in the 5’ UTR [15], within the coding sequence [16], and in some cases these sites may be present in multiple locations within a transcript. Target prediction algorithms are undoubtedly valuable tools to researchers in the field providing a rapid appreciation of the potential processes impacted by a particular miRNA and prioritising potential direct targets for validation assays.…”
Section: Introductionmentioning
confidence: 99%